The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1071100721996379
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty Radiographic Alignment Comparison Between Patient-Specific Instrumentation and Standard Instrumentation

Abstract: Background Several benefits are published supporting patient-specific instrumentation (PSI) in total ankle arthroplasty (TAA). This study seeks to determine if TAA with PSI yields different radiographic outcomes vs standard instrumentation (SI). Methods: Sixty-seven primary TAA patients having surgery using PSI or SI between 2013 and 2015 were retrospectively reviewed using weightbearing radiographs at 6-12 weeks postsurgery. Radiographic parameters analyzed were the medial distal tibia angle (MDTA), talar-til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The studies were each conducted with experienced surgeons. To what extent an influence exists with inexperienced surgeons could not be shown here [ 71 , 72 , 73 , 74 , 75 ].…”
Section: Total Ankle Arthroplasty (Taa)mentioning
confidence: 99%
“…The studies were each conducted with experienced surgeons. To what extent an influence exists with inexperienced surgeons could not be shown here [ 71 , 72 , 73 , 74 , 75 ].…”
Section: Total Ankle Arthroplasty (Taa)mentioning
confidence: 99%
“…19 The advantages of using PSI have been evaluated in several studies so far. 2,6,9,11,13,19 Two studies 6,13 investigated the accuracy of the final alignment when using PSI, without comparing to SR. Two further studies 11,19 presented a comparison with SR. Both studies concluded a similar accuracy between the techniques, although in the study of Hamid et al 11 the alignment was worse in the PSI group.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects considered include the higher accuracy of especially tibial implant positioning in PSI over SR and shorter operative times, which coincide with a reduced risk for wound healing disorders in PSI. 2 , 6 , 9 , 11 , 13 , 18 , 19 Disadvantages of PSI include the higher costs, the need for extensile periosteum stripping during surgery, and the need for a preoperative computed tomographic scan. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, postoperative radiographic alignment of TAA implants has not been found to be superior when comparing standard instrumentation to PSI utilizing NWBCT scans. 4 To our knowledge, there are currently no published reports defining the role of WBCT scans for preoperative TAA templating and PSI. The purpose of this study was to retrospectively assess accuracy and reproducibility of WBCT scans in determining implant position with preoperative patient-specific guides for TAA.…”
Section: Introductionmentioning
confidence: 99%